2016
DOI: 10.1007/s10802-016-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Callous Unemotional Behaviors and Executive Function in Early Childhood Predict later Aggression and Lower Peer-liking in Late-childhood

Abstract: Callous unemotional (CU) behaviors are linked to aggression, behavior problems, and difficulties in peer relationships in children and adolescents. However, few studies have examined whether early childhood CU behaviors predict aggression or peer-rejection during late-childhood or potential moderation of this relationship by executive function. The current study examined whether the interaction of CU behaviors and executive function in early childhood predicted different forms of aggression in late-childhood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 66 publications
(97 reference statements)
8
61
1
1
Order By: Relevance
“…Various studies indicated that poor inhibitory control is associated with high levels of aggressive behavior during the preschool period (Hughes et al, 2000;Raaijmakers et al, 2008;Waller, Hyde, Baskin-Sommers, & Olson, 2017). Impairments in inhibitory control have been proposed to explain the contradictory effects and null-findings regarding the association between empathy and aggression in the preschool period (Eisenberg, 2010;Eisenberg et al, 2010;Gill & Calkins, 2003;Lovett & Sheffield, 2007).…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…Various studies indicated that poor inhibitory control is associated with high levels of aggressive behavior during the preschool period (Hughes et al, 2000;Raaijmakers et al, 2008;Waller, Hyde, Baskin-Sommers, & Olson, 2017). Impairments in inhibitory control have been proposed to explain the contradictory effects and null-findings regarding the association between empathy and aggression in the preschool period (Eisenberg, 2010;Eisenberg et al, 2010;Gill & Calkins, 2003;Lovett & Sheffield, 2007).…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…Moreover, these effects were amplified in those with low levels of EF performance ratings, but at high levels of EF performance ratings, this effect was non-significant. Results from this study suggest that better EFs may serve as a protective factor for aggression and antisocial behaviour in children with elevated CU traits (Waller et al, 2017). However, other studies have found that elevated CU traits and deficits in EF are linked to more severe antisocial behaviour, including later violence and substance-abuse (Baskin-Sommers, Waller, Fish, & Hyde, 2015).…”
Section: Cu and Emotion Recognitionmentioning
confidence: 56%
“…Unexpectedly, the class with the relatively highest levels of CU (Class 4) had relatively better performance on all EF measures as compared to other classes. Existing studies have been mixed with regards to EF abilities in children and youth with elevated CU traits (Sulik & Obradović, 2017;Wakschlag et al, 2018;Waller, Hyde, Baskin-Sommers, & Olson, 2017). Waller and colleagues 2017 followed a cohort of high-risk children, collecting cross-informant and observational data, and found that CU traits at age 3 predicated aggression and peer rejection at age 10.…”
Section: Cu and Emotion Recognitionmentioning
confidence: 99%
“…Furthermore, planning and working memory skills (cool executive functioning skills) were predictive of proactive relational bullying in a British sample of young children (ages 3-6 years; Poland et al 2016). Conversely, weaker executive functioning in a highrisk sample of preschool-age children was predictive of various forms of bullying and aggression, including relational bullying, when they reached middle childhood (Waller et al 2017). This finding was supported by another investigation in which poor central executive working memory was associated with specific social impairments, including relational bullying, in typically developing fourth and fifth grade US students (McQuade et al 2013).…”
Section: Cognitive Correlates Of Indirect Bullyingmentioning
confidence: 96%